Social Determinants of Domestic Violence Among Saudi Married Women in Riyadh, Kingdom of Saudi Arabia - Alquaiz, Aljohara M. (Journal of interpersonal violence, 2021)
Intimate partner violence is a worldwide public health problem. The objectives of this study were to measure the prevalence and types of domestic violence, and to explore the association between social determinants (sociodemographic factors, husband-related factors, and social support) and violence against women by their intimate partner (husband). We conducted a cross-sectional survey in 18 randomly selected primary health care centers and 13 private institutions (teaching institutes, government offices, social welfare organizations) in Riyadh, Saudi Arabia. Female data collectors took interview from 1,883 married Saudi females aged 30 to 75 years. Interviews included sociodemographic information, reproductive health variables, and social support questionnaire. Violence was measured using modified Intimate Partner Violence Against Women questionnaire developed by the World Health Organization. Multivariate logistic regression analysis was conducted. The lifetime prevalence for any type of violence was 43.0% (n = 810). The most frequent type was controlling behavior (36.8%), followed by emotional violence (22%), sexual violence (12.7%), and physical violence (9.0%). Multivariate logistic regression analysis revealed that the following were associated with greater odds of reporting domestic violence: younger age 30 to 40 years (adjusted odds ratio [aOR] = 1.9, 95% confidence interval [CI] = [1.3, 3.0]), 41 to 50 years (aOR = 1.6, 95% CI = [1.1, 2.5]); lack of emotional support (aOR = 1.7, 95% CI = [1.2, 2.5]); lack of tangible support (aOR = 1.4, 95% CI = [1.1, 1.9]); and perceived poor self-health (aOR = 1.7, 95% CI = [1.0, 3.0]), husbands’ poor health (aOR = 1.9, 95% CI = [1.2, 2.0]), and polygamy (aOR = 1.6, 95% CI = [1.5, 2.6]). Domestic violence occurs frequently in Saudi Arabia. Both social conditions and social relations are significantly associated with domestic violence against Saudi women. Furthermore, improvement in implementation of the local policies and multisectoral protection services can prevent women from domestic violence.